Malignancy-Induced Hypercalcemia—Diagnostic Challenges - Hoyoux, Claire; Lombet, Jacques; Nicolescu, Corina Ramona (Frontiers in Pediatrics, 2017)
Hypercalcemia in children is a rare metabolic finding. The clinical picture is usually nonspecific, and the etiology includes several entities (metabolic, nutritional, drug-induced, inflammatory, cancer-associated or genetic) depending on the age at presentation, but severe hypercalcemia is associated mainly with malignancy in childhood and sepsis in neonates. Severe parathyroid hormone (PTH)-suppressed hypercalcemia is challenging and requires multidisciplinary diagnostic and therapeutic approaches to: (i) confirm or rule out a malignant cause; (ii) treat it and its potentially dangerous complications. We report a case of severe and complicated PTH-independent hypercalcemia in a symptomatic 3-year-old boy. His age, severity of hypercalcemia and its complicated course, and the first imaging reports were suggestive of malignancy. The first bone and kidney biopsies and bone marrow aspiration were normal. The definitive diagnosis was a malignant-induced hypercalcemia and we needed 4 weeks to assess other differential diagnoses and to confirm, on histopathologic and immunochemical base, the malignant origin of hypercalcemia. Using this case as an illustrative example, we suggest a diagnostic approach that underlines the importance of repeated histology if the clinical suspicion is malignancy-induced hypercalcemia. Effective treatment is required acutely to restore calcium levels and to avoid complications.